Integrating Local Craftsmanship into Physics Education: The Role of Kasongan Pottery in Developing Lateral Thinking Skills - Setyaningsih, Ani; Fakıoglu, Turgut; Karyanti, Dwi; Hantari, Harini Wigya (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to explore scientific knowledge in the process of making Kasongan pottery and its potential in improving the lateral thinking skills of junior high school students through the integration of local crafts in physics learning. Methodology: This study uses a descriptive qualitative approach with semi-structured interviews, observation, and documentation. Purposive sampling technique with 38 craftsmen. Data analysis using the interactive model of Miles and Huberman. Main Findings: Scientific knowledge in the process of making pottery includes concepts of physics, chemistry, and biology. This process can improve students' lateral thinking skills through the application of practical problems and solutions. Novelty/Originality of this study: This study introduces the integration of local crafts, especially Kasongan pottery, in physics education to improve lateral thinking skills. This approach connects scientific concepts with traditional practices, offering a new method in learning and preserving culture.